Genetic and Probiotic Characteristics of Urolithin A Producing Enterococcus faecium FUA027 - Mengjie Xia; Shuting Mu; Yaowei Fang; Xiaomeng Zhang; Guang Yang; Xiaoyue Hou; Fuxiang He; Yaling Zhao; Yichen Huang; Wei Zhang; Juan Shen; Shu Liu (Foods, 2023)
Enterococcus faecium FUA027 transforms ellagic acid (EA) to urolithin A (UA), which makes it a potential application in the preparation of UA by industrial fermentation. Here, the genetic and probiotic characteristics of E. faecium FUA027 were evaluated through whole-genome sequence analysis and phenotypic assays. The chromosome size of this strain was 2,718,096 bp, with a GC content of 38.27%. The whole-genome analysis revealed that the genome contained 18 antibiotic resistance genes and seven putative virulence factor genes. E. faecium FUA027 does not contain plasmids and mobile genetic elements (MGEs), and so the transmissibility of antibiotic resistance genes or putative virulence factors should not occur. Phenotypic testing further indicated that E. faecium FUA027 is sensitive to clinically relevant antibiotics. In addition, this bacterium exhibited no hemolytic activity, no biogenic amine production, and could significantly inhibit the growth of the quality control strain. In vitro viability was >60% in all simulated gastrointestinal environments, with good antioxidant activity. The study results suggest that E. faecium FUA027 has the potential to be used in industrial fermentation for the production of urolithin A.